Inside the Organizational Institutions of Institutional Economics: Why Are There Two Institutionalist Associations?. Issue 2 (2nd April 2016) - Almeida, Felipe
Abstract: The institutionalist-inspired Association for Evolutionary Economics (AFEE), officially founded in 1965, was the first heterodox association to break with the American Economic Association (AEA). In 1979, another institutionalist association, the Association for Institutional Thought (AFIT), was founded. Using mainly archival evidence, this paper provides historical reasons for the presence of two institutionalist associations.